Phonological development in hearing-impaired Malay-speaking children - Jhanani S.Nagaraja,; Badrulzaman Abdul Hamid,; Nashrah Maamor, (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study explores the phonological development of hearing-impaired Malay-speaking children, shedding light on the unique challenges and patterns that characterise their phonological process. The subjects of the research include 40 hearing aids Malay-speaking children with a chronological age of 5 to 9 years old and hearing age of a minimum of 2 years. Utilising a mixed-method research method, we examined the effect of hearing-impairment on the acquisition of Malay phonological features and the association between socio-demographic factors and phonological process in hearing-impaired Malay-speaking children. Through the analysis of speech samples and sociodemographic information that were collected through a standardised picture naming task, it was concluded that the phonological process in hearing-impaired Malay-speaking children is fronting, assimilation, stopping, voicing, initial consonant deletion, epenthesis, deaffrication, depalatalisation, denasalization, devoicing, prevocalic voicing, final consonant deletion, reduplication, and gliding. Furthermore, there is a relationship between socio-demographic factors and the phonological process in hearing-impaired Malay-speaking children. Lastly, hearing age is an important variable that is statistically significant in predicting the relationship between sociodemographic factors and phonological process in hearing-impaired Malay-speaking children. The results of this research contribute to a deeper comprehension of the phonological development of hearing-impaired children in a Malay-speaking context, with its relationship to sociodemographic factors.